If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x) = 5(2x + -3) Reorder the terms: 5x = 5(-3 + 2x) 5x = (-3 * 5 + 2x * 5) 5x = (-15 + 10x) Solving 5x = -15 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 5x + -10x = -15 + 10x + -10x Combine like terms: 5x + -10x = -5x -5x = -15 + 10x + -10x Combine like terms: 10x + -10x = 0 -5x = -15 + 0 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| R=b^2+1 | | (5x)2=15x-45 | | 3c-1=c | | 3x-5-x=2x-3 | | 3ysquared= | | 3(2x+1)-2(3-2)=13 | | 15x-45/2=5x | | 1/3x3/8 | | (7a)x(2b)=0 | | 15/105 | | 9z+4-5z-5= | | -6(r-7)=-54 | | 8+9a=7 | | 4x+3+2y=11 | | 7x-4.23=0.2+2.57 | | 7x-4.23=0.2 | | -8(n-2)-2=-21-3n | | 3x=2(7x-3) | | 80+5x=7x | | 4(5r-5)=-20-7r | | -5=7-2x | | (3x-1)(x+2)=-1 | | -x-3(-5x-8)=136 | | (12^5)/(9^2)*(4^4) | | 12^5/9^2*4^4 | | 0.3x-2(0.1x+0.4)= | | (3a-9)/(3a-6)*(a/a^2-9) | | {(3a-9)/(3a-6)}*(a/a^2-9) | | f(x)=-3.25(-4.2) | | 18=2v+4 | | 6+2(5x-1)=84 | | 18-12a= |